Gamma knife radiosurgery for high-risk lactotroph adenomas: Long-term results. (April 2021) - Kara, Mujdat; Samanci, Yavuz; Yilmaz, Meltem; Sengoz, Meric; Peker, Selcuk
Highlights: About 10% of lactotroph adenomas exhibit DA resistance. HRLAs exhibit invasion to neighboring tissues and recurrence and resistance to traditional therapies. GKRS for HRLAs seems to be a safe and effective option with low morbidity. Abstract: Gamma Knife radiosurgery (GKRS) for lactotroph adenomas (LAs) or prolactinomas is limited due to the effectiveness of medical treatments and surgery. Cases who are refractory to medical treatment and/or surgery may be managed with GKRS. We aimed to describe the effectiveness of GKRS for high-risk lactotroph adenomas (HRLAs) and LAs that were medically and surgically refractory. We analyzed our series of patients with HRLAs and LAs who were managed with GKRS following failed medical treatment and surgery and who had at least three years of follow-up. A total of 52 patients (22 HRLAs and 30 LAs) were included in the analysis of radiological, endocrine, and clinical outcomes. Radiological control was achieved in 68.2% of subjects in the HRLA group and 96.7% of subjects in the LA group. Hormonal control was achieved in 68.2% of patients in the HRLA group and 80% of patients in the LA group. On univariate analysis, hormonal control was significantly associated with pre-treatment volume (p = 0.007), higher margin dose (p = 0.002) and Ki-67 proliferative index (p = 0.007). Complications involved new pituitary hormone deficiencies in 19.2% of patients and asymptomatic peripheral visual field defect in 1.9% of patients. To the best of our knowledge, this is the first study to examine the effectiveness of GKRS in LAs and HRLAs, with the highest median follow-up in the literature. High hormonal control rate, even in HRLAs, and lower complication rates suggest that GKRS should be part of the techniques for managing treatment refractory LAs.